2020
DOI: 10.1029/2020jb020684
|View full text |Cite
|
Sign up to set email alerts
|

Mg and Zn Isotope Evidence for Two Types of Mantle Metasomatism and Deep Recycling of Magnesium Carbonates

Abstract: To test the ability of Mg and Zn isotopes in discriminating between different types of mantle metasomatism and identifying deep carbon cycling, here we present a comparative study on two types of Cenozoic lavas in SE Tibet, that is, K-rich (potassic-ultrapotassic) lavas and Na-rich alkali basalts. The contrasting bulk rock chemical compositions, Sr-Nd isotopic ratios, and olivine chemistry between them suggest distinct sources in the lithospheric mantle and asthenosphere, respectively. The K-rich lavas have ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 143 publications
(354 reference statements)
5
8
0
Order By: Relevance
“…5,6). As the basalts in Eastern China are produced by partial melting of asthenospheric mantle (e.g., , the Maguan alkali basalts are more likely derived from asthenospheric mantle, nor lithospheric mantle, which agrees well with the previous studies (e.g., Liu et al, 2020).…”
Section: Identifying the Mantle Source Of The Maguan Alkali Basaltssupporting
confidence: 89%
See 3 more Smart Citations
“…5,6). As the basalts in Eastern China are produced by partial melting of asthenospheric mantle (e.g., , the Maguan alkali basalts are more likely derived from asthenospheric mantle, nor lithospheric mantle, which agrees well with the previous studies (e.g., Liu et al, 2020).…”
Section: Identifying the Mantle Source Of The Maguan Alkali Basaltssupporting
confidence: 89%
“…The fields of oceanic basalts are modified from Hofmann et al (1986). The sources of literature data: Miocene basalts in the Maguan area (Wang et al, 2001;Wei and Wang, 2004;Xia and Xu, 2005;Flower et al, 2013;Huang, 2012;Liu et al, 2020), Eocene-Oligocene mantle-derived potassic magmas in Western Yunnan (Wang et al, 2001;Xia and Xu, 2005;Guo et al, 2005;Huang et al, 2010;Liu et al, 2020), and Tengchong J o u r n a l P r e -p r o o f mafic volcanic suites (Chen et al, 2002;Li and Liu, 2012;Zhou et al, 2012;Zou et al, 2014;Tian et al, 2018). To avoid the effects of significant magma differentiation and crustal contamination, the aforementioned literature data are plotted with SiO 2 <55 wt.% and MgO >5 wt.% on an anhydrous basis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sr and Nd isotopic ratios were corrected for mass fractionation using 86 Sr/ 88 Sr = 0.1194 and 146 Nd/ 144 Nd = 0.7219. Reference standards BHVO-2 and SRM987 for Sr yielded 87 Sr/ 86 Sr = 0.703508 ± 10 (2SD) and 0.710257 ± 18 (2SD) respectively, corresponding to previously reported values (e.g., Li et al, 2017;Li and Han, 2021;Liu et al, 2020) and the recommend values suggested by Zhang and Hu (2020) (0.703480 ± 16 and 0.710248 ± 24 respectively). The average 143 Nd/ 144 Nd of standard BHVO-2 is 0.512964 ± 5 (2SD), corresponding to the recommend value of 0.512983 ± 20 (2SD, n = 94) (Zhang and Hu, 2020).…”
Section: Journal Pre-proofsupporting
confidence: 82%